Process mapping applied to traffic fine management in a basic sanitation company - Bastos, João Vinícius Ferreira; Sakuraba, Celso Satoshi (Brazilian Journal of Production Engineering, 2025)
Traffic fines management is crucial in controlling a fleet and ensuring efficiency in all its stages. Without such management, companies can face significant losses as offending drivers are not identified, guided, or reeducated, leading to increased recurrence of infractions. After a bibliographic review of related works, this study mapped the processes of the vehicle sector in a basic sanitation company in Sergipe, aiming to implement effective management of fines received by drivers. Several gaps responsible for inadequate handling were identified. Implementations included document management, standardization of procedures and communication, and the creation of a digital data organization tool focused on traffic fines. These changes resulted in significant improvements, such as reduced response times between stages, decreased costs due to overdue fines, and more effective data control. Despite these improvements, the sector still requires advancements to achieve the expected effectiveness, such as integrated systems and changes in organizational culture.